Numerical study of the moisture content threshold under prescribed burning conditions. (June 2021) - Awad, Carmen; Frangieh, Nicolas; Marcelli, Thierry; Accary, Gilbert; Morvan, Dominique; Meradji, Sofiane; Joseph Chatelon, François; Louis Rossi, Jean
Abstract: The safety during prescribed burnings could be achieved by conducting these operations under marginal conditions of fire propagation. This type of fire can or cannot propagate on account of small deviations of the burning conditions, mainly the wind speed, the fuel load, and the fuel moisture-content. In this context, numerical simulations of grassland fires were conducted under marginal conditions in order to relate the moisture-content threshold of propagation success to the wind speed and the fuel load. The simulations were conducted using FireStar2D, a complete physical 2D fire simulator based on a multiphase modelling approach. The 10 m-open wind speed ranged from 0 to 10 m/s and the fuel load varied from 0.1 kg/m 2 to 0.7 kg/m 2 . The effects of wind speed and fuel moisture-content on the fire behaviour and on the flame parameters are discussed. The results show that the moisture threshold increases with the fuel load until it reaches a value beyond which there is no dependence. A similar dependence of the moisture threshold on the wind speed is also observed. Finally, empirical formulae were constructed to relate the fuel moisture content threshold to the wind speed and the fuel loading implicitly through Byram's convective number.